2013
DOI: 10.5194/acp-13-7225-2013
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing the transition layer at extratropical latitudes using MLS O<sub>3</sub> and MOPITT CO analyses

Abstract: Abstract. The behavior of the extratropical transition layer (ExTL) is investigated using a chemistry transport model (CTM) and analyses derived from assimilation of MLS (Microwave Limb Sounder) O3 and MOPITT (Measurements Of Pollution In The Troposphere) CO data. We firstly focus on a stratosphere–troposphere exchange (STE) case study that occurred on 15 August 2007 over the British Isles (50° N, 10° W). We evaluate the effect of data assimilation on the O3–CO correlations. It is shown that data assimilation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…For ozone, the use of state augmentation, with a careful way of minimizing sampling errors, may address nonlinear effects since errors and chemical feedbacks are negatively correlated [Zoogman et al, 2014]. The use of CO and O 3 error correlations in conjunction with collocated observations can also improve both CO and O 3 spatiotemporal distribution and budgets [e.g., Barré et al, 2013]. 3.…”
Section: Discussionmentioning
confidence: 99%
“…For ozone, the use of state augmentation, with a careful way of minimizing sampling errors, may address nonlinear effects since errors and chemical feedbacks are negatively correlated [Zoogman et al, 2014]. The use of CO and O 3 error correlations in conjunction with collocated observations can also improve both CO and O 3 spatiotemporal distribution and budgets [e.g., Barré et al, 2013]. 3.…”
Section: Discussionmentioning
confidence: 99%
“…This model and its assimilation system have been successfully used for tropospheric and stratospheric research (e.g. Bousserez et al, 2007;Barré et al, 2013Barré et al, , 2014Lacressonnière et al, 2014) and also for operational purposes (Rouïl et al, 2009).…”
Section: Mocage Forecast and Analysis Systemmentioning
confidence: 99%
“…The system, recently renamed VALENTINA, has been used to compute global and regional re-analyses of atmospheric composition in multiple studies (El Amraoui et al, 2008;Massart et al, 2009;Barré et al, 2013Barré et al, , 2014Emili et al, 2014). The assimilation algorithm employed for MACC-II analyses is a 3DVar with assimilation windows of 1 h length (Jaumouillé et al, 2012), corresponding to the frequency of surface measurements.…”
Section: Mocage Forecast and Analysis Systemmentioning
confidence: 99%
“…[], and Barré et al . [] demonstrated the ability of assimilated ozone data from limb sounders to represent individual deep stratospheric intrusion events. The work delineated above illustrates the value of a multiyear analysis and a statistical evaluation of the capabilities that assimilation of MLS data offers.…”
Section: Introductionmentioning
confidence: 99%
“…Olsen et al [2008] used the Global Modeling Initiative (GMI) model driven by GEOS-4 assimilated winds at this resolution and showed that the analysis winds have sufficient transport information in the vertical to reproduce a lamina transport event observed by HIRDLS in the lower stratosphere. Case studies done by Semane et al [2007], El Amraoui et al [2010], and Barré et al [2013] demonstrated the ability of assimilated ozone data from limb sounders to represent individual deep stratospheric intrusion events. The work delineated above illustrates the value of a multiyear analysis and a statistical evaluation of the capabilities that assimilation of MLS data offers.…”
Section: Introductionmentioning
confidence: 99%